Control of volunteer Clearfield® oilseed rape in sugar beet - Buhre, Cord; Bremer, Hagen; Ladewig, Erwin (Julius-Kühn-Archiv, 2012)
The Clearfield® production system for winter oilseed rape is now registered in France and a introduction for Germany is planned. In this production system, imidazolinone herbicides are used. These herbicides belong to the same mode of action (HRAC group B) as the active ingredient triflusulfuron-methyl in the herbicide Debut®. Therefore, a reduced efficacy of this active ingredient for the control of Clearfield® volunteer oilseed rape is expected. Today non-Clearfield® volunteer oilseed rape in sugar beets is effectively controlled with triflusufuronmethyl. Due to the fact that oilseed rape and sugar beet are increasingly cultivated in the same crop rotation, Clearfield® volunteer oilseed rape could be expected in future sugar beet crop rotations. To determine the performance of different herbicide treatments for a sufficient control of Clearfield® volunteer oilseed rape in sugar beet, in 2010 and 2011 14 field-trials were conducted in four countries, Germany, Poland, Romania and Slovakia. These trials had been set up in a two way split-plot design with non-Clearfield®-rape and Clearfield® oilseed rape. The effects of ten treatments with different herbicides and application dates were tested. The results of both years showed large differences in the herbicide efficacy among the herbicide treatments. Pre-emergence application led to insufficient results in both years on both cultivars. Applied post-emergence, the herbicide treatment with Debut® (triflusulfuron-methyl) controlled non-Clearfield® volunteer rape considerable better, than the Clearfield® volunteer rape. A combination of herbicides in addition with Venzar® (Lenacil) provided good control of volunteer Clearfield® oilseed rape.